2012
DOI: 10.1174/113564012802845659
|View full text |Cite
|
Sign up to set email alerts
|

Identificación e interpretación de las posibles desigualdades formativas en ciencias de chicos y chicas en la educación obligatoria y el bachillerato

Abstract: Siguiendo el interés que a nivel internacional han suscitado recientemente los estudios de género, el artículo analiza las diferencias educativas entre chicos y chicas en las ciencias experimentales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
2
0
3
Order By: Relevance
“…In a deeper descriptive analysis of the data, a higher percentage of agreement among girls in the perception of a demanding society towards women was reflected in the gender perspective items G3 (in a world traditionally considering men, women would work better because they have to show that they are competitive) and G11 (society has different expectations for men and women, in relation to their professions). These results partially confirm those obtained in other studies reporting gender differences with respect to stereotyped statements [18,20], as well as with respect to the analysis of the performance and/or attitude towards science of CSE students [5,12,17,37]. Furthermore, Sanchez et al [19] found a strong presence of career-related stereotypes in students aged 16-32, although they reported a higher persistence of stereotypes in boys, contrary to what was found in our research.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In a deeper descriptive analysis of the data, a higher percentage of agreement among girls in the perception of a demanding society towards women was reflected in the gender perspective items G3 (in a world traditionally considering men, women would work better because they have to show that they are competitive) and G11 (society has different expectations for men and women, in relation to their professions). These results partially confirm those obtained in other studies reporting gender differences with respect to stereotyped statements [18,20], as well as with respect to the analysis of the performance and/or attitude towards science of CSE students [5,12,17,37]. Furthermore, Sanchez et al [19] found a strong presence of career-related stereotypes in students aged 16-32, although they reported a higher persistence of stereotypes in boys, contrary to what was found in our research.…”
Section: Discussionsupporting
confidence: 87%
“…She found that the intrinsic stereotypes were much weaker in engineering than in humanities students, and that this strength was correlated with poor mathematics performance. Referring to Spain, Marbà-Tallada et al [17] analyzed a similar situation, highlighting the lack of a profound explanation on the role of gender stereotypes associated with science and the scientific profession; while it has been widely studied in other professions [18][19][20].…”
Section: Gender Stereotypes In Science Educationmentioning
confidence: 99%
“…llegando incluso a no ser consideradas por algunos de los profesores de género masculino como un igual capacitado para tratar cuestiones profesionales o de investigación (Blättel-Mink, 2002;DonosoVázquez, Figuera, & Rodríguez, 2011;Jackson, 2000;Marbà-Tallada & Solsona-Pairó, 2012;Mischau, 2001). Destacando incluso como los estudiantes varones tratan de manera diferente a sus profesoras que a sus profesores (Erwin & Stewart, 1997); o como las estudiantes llegan a considerar que su trabajo es valorado diferente al de sus compañeros (Fernández García, Hernández García, & Rodríguez Pérez, 2014;Rodd & Bartholomew, 2006).…”
Section: Género Sociedad Y Enseñanza Superiorunclassified
“…Abarcando la hipótesis planteada: la actitud del profesorado universitario hacia la docencia universitaria depende del género del docente, en las dos últimas décadas, como se ha podido comprobar, se han elevado el interés por las diferencias educativas entre hombres y mujeres, su éxito escolar y por la continuidad de estudios preferenciales (Marbà-Tallada & Solsona-Pairó, 2012). El interés y el seguimiento de estos temas se ve motivado en parte por la falta de interés y de éxito de mujeres en diferentes temas; así como la aparición de investigaciones que corroboran la existencia de cierta barrera de género (Donoso-Vázquez et al, 2011;Erwin & Maurutto, 1998;Fernández García et al, 2014;Inda, Rodríguez, & Peña, 2010;Jackson, 2000).…”
Section: Discusión Y Conclusionesunclassified
“…En definitiva, las mujeres son percibidas como elementos extraños en una cultura académica dominada por lo masculino y en la que tienen una pequeña posibilidad de impacto y cambio, no siendo consideradas por algunos de los profesores de género masculino como un igual con el que discutir cuestiones profesionales o de investigación (Erwin y Stewart, 1997;Jackson, 2000;Blättel -Mink, 2002;Ferreira, 2003;Marbá y Solsona, 2012;Mischau, 2001). En ciertos casos, se aprecia incluso cómo también los estudiantes varones tratan de manera diferente a sus profesoras (Erwin y Stewart, 1997) y, en este mismo sentido, las alumnas de estudios científicos manifiestan sentirse invisibles o ser tratadas de manera desigual por determinados profesores: no escucha de sus respuestas, descripción como mejor alumno de la clase referida a un varón a pesar de que el resultado académico más brillante sea el de una chica, profesores que se desplazan por el aula únicamente hacia el lugar ocupado por los chicos, la preconcepción de que la capacidad de las alumnas es innatamente menor, etc.…”
Section: Introducción ¿Es La Universidad Un Espacio Neutral No Sujetounclassified